1998
DOI: 10.1038/sj.onc.1202477
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E2: a novel CDK2 partner in the late G1 and S phases of the mammalian cell cycle

Abstract: We report here the cloning and characterization of human and mouse cyclin E2, which de®ne a new subfamily within the vertebrate E-type cyclins, while all previously identi®ed family-members belong to the cyclin E1 subfamily. Cyclin E2/CKD2 and cyclin E/CDK2 complexes phosphorylate histone H1 in vitro with similar speci®c activities and both are inhibited by p27 Kip1 . Cyclin E2 mRNA levels in human cells oscillate throughout the cell cycle and peak at the G1/S boundary, in parallel with the cyclin E mRNA. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 32 publications
2
114
1
1
Order By: Relevance
“…Cdk2 and Cdk3 activities increase rapidly in mid to late G1 phase and peak close to the G1 to S transition (reviewed in [43]). Both Cdk2 and Cdk3 form complexes with cyclins A and E as well as with more recently identified cyclins A1 [44] and E2 [45]. Furthermore, both Cdk2 and Cdk3 are inhibited by p21 Cip1 and p27 Kip1 CKIs [46].…”
Section: Ink4 Family Of Ckimentioning
confidence: 84%
“…Cdk2 and Cdk3 activities increase rapidly in mid to late G1 phase and peak close to the G1 to S transition (reviewed in [43]). Both Cdk2 and Cdk3 form complexes with cyclins A and E as well as with more recently identified cyclins A1 [44] and E2 [45]. Furthermore, both Cdk2 and Cdk3 are inhibited by p21 Cip1 and p27 Kip1 CKIs [46].…”
Section: Ink4 Family Of Ckimentioning
confidence: 84%
“…Our study is the first to date that analyzed the effect of CCNE2 mRNA on RFI in primary breast cancer patients. CCNE2 is encoded by a different gene than CCNE1 and was only recently characterized by Lauper et al 28 Although CCNE1 and CCNE2 proteins share 47% similarity and are both implicated in G1/S progression of the cell cycle, it has been speculated that CCNE2 could not be simply redundant with CCNE1, but might regulate distinct rate-limiting pathways in G1/S control. For example, here we showed that expression levels of CCNE1 but not CCNE2 were associated with the expression of the proliferation marker Ki67.…”
Section: Discussionmentioning
confidence: 99%
“…5,[8][9][10] Deletion or mutation of the F-box protein Fbw7, part of the Skp1-Cul1-Rbx1 ubiquitin ligase complex (SCF Fbw7 ) that targets cyclin E for proteosomal degradation, 11,12 is also highly correlated with chromosome instability. 13 Although cyclins E1 and E2 are often coordinately regulated, share strong sequence similarity in functional important regions, including the cyclin box and centrosomal localization sequence, 14 and appear to be functionally redundant during murine development, 1,[15][16][17][18][19] there is accumulating evidence that, like many cyclins, they have distinct roles under some circumstances. 20 For example, during liver regeneration, cyclin E1 promotes endoreduplication, while cyclin E2 suppresses it.…”
Section: Introductionmentioning
confidence: 99%